South Africa's Restrictions on Interest Deductions and Their Compatibility with the Non-Discrimination Provisions of the 2017 Version of the OECD Model - Friedman, Joshua Michael (Department of Commercial Law, 2021)
This dissertation examines whether South Africa's interest deduction tax laws are compatible with selected aspects of their Double Taxation Treaties that are based on the 2017 OECD Model Tax Convention. This dissertation will outline and examine the innerworkings of three of South Africa's domestic interest deduction legislative provisions namely, sections 23N, 31 and 23M of the Income Tax Act. Thereafter, the relevant Non-Discrimination provisions of the 2017 OECD Model Tax Convention contained in Article 24 will be discussed. The exemptions to Article 24 will also be dealt with before addressing the impact of the recently added ‘Savings Clause'. The understandings gained from the above will then be used to test South Africa's interest deduction legislative provisions against the relevant Articles of the OECD Model Tax Convention. This dissertation concludes the following: section 23N does not constitute discrimination; section 31 necessarily does but falls within one of the exemptions to Article 24; and section 23M violates the non-discrimination provision contained in Article 24(4) and as such, is not compatible with any of South Africa's Doubled Taxation Treaties that contain the relevant Articles. This dissertation ends off with recommendations on how South Africa deals with the conflict, the best of which is to amend section 23M to include an arm's length requirement.